Symbolic Ornamentation In Islamic Art Ornementation Symbolique Dans L'art Islamique (Journal of Namibian Studies : History Politics Culture, 2024)
Islamic art is a product of a religious and social environment that emerged with the advent of Islam. It is distinguished by various characteristics that set it apart from other art forms, such as abstraction, aversion to depicting human and animal figures, diversity, and plurality. Muslim artists utilized Arabic script in its various forms and types to decorate their subjects, incorporating symbolic themes, especially geometric and astronomical ones like stars, crescents, and the palm of the hand, with the addition of colors used symbolically or to mimic the original model, highlighting its nature and size, in addition to depicting reality as it is.All these elements fall within the realm of Islamic art and its special symbolism in artifacts and relics, whether fixed or movable.